Investigation into hydride reorientation in dummy fuel rod cladding (Zr-1%Nb) under internal pressure during testing simulating SNF handling and accidents with limiting cladding heating up to 410 °С - Riedkina, G.P.; Chernyayeva, Т.P.; Grytsyna, V.M.; Krasnorutskyy, V.S.; Petelguzov, I.A.; Slabospytska, O.O. (Вопросы атомной науки и техники, 2020)
This paper presents the results of experimental investigations into hydride reorientation that (HRT) can occur in fuel rod claddings under conditions simulating normal and some accident SNF handling modes with limiting cladding heating up to 410 °C. Dummy fuel rods with Zr-1%Nb cladding with different hydrogen content under internal pressure (cold pressure under cladding of 3, 4, and 5 МPа) were subjected to testing with heating up to 410 °С, holding at this temperature during 8 h and subsequent cooling. It was found that at a hydrogen concentration of 400 ppm, intensive hydride reorientation in the dummy fuel rod claddings during thermal test begins at a tangential stress of ≈ 55...60 MPa at 410 °C. As the hydrogen concentration decreases, the intensity of test impact on hydride reorientation decreases significantly. SNF thermal cycling and holding in DSFSF significantly increases hydride reorientation. In the claddings with a 400 ppm hydrogen concentration subjected to 3 thermal cycles 180↔410 °C, almost complete hydride reorientation occurs. Mechanical testing of samples with different hydrogen content was conducted before and after the hydride reorientation test. Представлено результати експериментальних досліджень переорієнтації гідридів, яка може мати місце в оболонках твелів в умовах, що імітують штатні і деякі аварійні режими поводження з ВЯП і граничним нагріванням оболонок до 410 °С. Проведено випробування з нагріванням макетів твелів з оболонками зі сплаву Zr-1%Nb з різним вмістом водню під внутрішнім тиском (холодний тиск під оболонкою 3, 4 і 5 МПа) до температури 410 °С, витримкою при цій температурі 8 год і наступним охолодженням. Встановлено, що при вмісті водню 400 ppm інтенсивна переорієнтація гідридів в оболонках макетів твелів при термічних випробуваннях починається при тангенціальній напрузі ≈ 55...60 МПа при 410 °С. Зі зменшенням вмісту водню інтенсивність впливу випробувань на переорієнтацію гідридів значно знижується. Термоциклування та витримка ВЯП у ССВЯП призводять до значного посилення переорієнтації гідридів. В оболонках з концентрацією водню 400 ppm, при випробуваннях з трикратним термоциклуванням 180↔410 °С відбувається практично повна переорієнтація гідридів. Проведено механічні випробування зразків з різним вмістом водню до і після випробувань. Представлены результаты экспериментальных исследований переориентации гидридов, которая может происходить в оболочках твэлов в условиях, имитирующих штатные и некоторые аварийные режимы обращения с ОЯТ и предельным нагреванием оболочек до 410 °С. Проведены испытания с нагревом макетов твэлов с оболочками из сплава Zr-1%Nb и различным содержанием водорода под внутренним давлением (холодное давление под оболочкой 3, 4 и 5 МПа) до температуры 410 °С, выдержкой при этой температуре 8 ч и последующим охлаждением. Установлено, что при содержании водорода 400 ppm интенсивная переориентация гидридов в оболочках макетов твэлов при термических испытаниях начинается при тангенциальном напряжении ≈ 55...60 МПа и 410 °С. С уменьшением содержания водорода интенсивность воздействия испытаний на переориентацию гидридов значительно снижается. Термоциклирование и выдержка ОЯТ в СХОЯТ приводят к усилению переориентации гидридов. В оболочках с концентрацией водорода 400 ppm, при испытаниях с трехкратным термоциклированием 180↔410 °С происходит практически полная переориентация гидридов. Проведены механические испытания образцов с различным содержанием водорода до и после испытаний.